Characteristics of microplastics and the role for complex pollution in e-waste recycling base of Shanghai, China. (November 2022) - Zhan, Lu; Zhang, Qi; Bulati, Akemareli; Wang, Rui; Xu, Zhenming
Graphical abstract: Abstract: Plastics used in electric and electronic products cover a wide range, and contain many additives, such as brominated flame retardant and so on. These compounds and microplastics may be released into environment when the electric and electronic products are obsoleted and recycled. This study explores the characteristics of microplastics and the complex pollutions in a formal e-waste recycling base in Shanghai, China. The maximum abundance of microplastics is observed in dust samples of the recycling base and the average abundance is 44277 ± 69032p/50 g. 103 kinds of polymers are identified, including 4 kinds of packaging plastics, 32 kinds of engineering plastics, 18 kinds of rubber, and 49 kinds of other polymers. It is found that microplastics show weak adsorption effect for heavy metals. However, microplastics are important carrier of ∑8 PBDEs released during the whole recycling processes, and BDE-209 account for more than 50 % of PBDEs in microplastics. It is estimated that the microplastics load inside the e-waste recycling base was 4.01 tons based on the measured statistics. This study will provide theoretical basis for further understanding the potential pollution of microplastics and upgrading the corresponding control measures.